2020
DOI: 10.4067/s0718-27242020000300052
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Innovation and Tech Innovation Persistence

Abstract: In developing economies, little is invested in research and development. Therefore, it is proposed that lower-tech firms develop their absorptive capacity and be linked through market and institutional networks to achieve technological innovation persistence. This study uses an ordinal logistics model applied to a sample of Peruvian manufacturing firms, concluding that there is an effect on product and process innovation persistence. Thus, executives can emphasize organizational innovation and absorptive capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Secondly, absorptive capacity must display a clear link with product innovation (Hair, Black, Babin, & Anderson, 2019;Sekaran & Bougie, 2016). In this particular context, a preponderance of empirical evidence corroborates the linkage between human capital and absorptive capacity (Ahmed et al, 2020;Bye & Faehn, 2022;Kato, 2020;Oliveira et al, 2020;Wu, 2020), while concurrently establishing the nexus between absorptive capacity and product innovation (Akram et al, 2021;Coronado-Medina et al, 2020;Gallegos et al, 2020;Gao et al, 2022;Jeong et al, 2019). Hence, it is plausible to deduce that absorptive capacity indeed mediates the intricate relationship existence between human capital and the realization of product innovation.…”
Section: Conceptual Frameworkmentioning
confidence: 74%
See 3 more Smart Citations
“…Secondly, absorptive capacity must display a clear link with product innovation (Hair, Black, Babin, & Anderson, 2019;Sekaran & Bougie, 2016). In this particular context, a preponderance of empirical evidence corroborates the linkage between human capital and absorptive capacity (Ahmed et al, 2020;Bye & Faehn, 2022;Kato, 2020;Oliveira et al, 2020;Wu, 2020), while concurrently establishing the nexus between absorptive capacity and product innovation (Akram et al, 2021;Coronado-Medina et al, 2020;Gallegos et al, 2020;Gao et al, 2022;Jeong et al, 2019). Hence, it is plausible to deduce that absorptive capacity indeed mediates the intricate relationship existence between human capital and the realization of product innovation.…”
Section: Conceptual Frameworkmentioning
confidence: 74%
“…A moderating effect may occur in conditions where the independent variable has an influence on the dependent variable, and an intended moderating variable has a relationship on the both of independent and dependent variable (Hair et al, 2019;Sekaran & Bougie, 2016). In this case, human capital has an effect on product innovation (Atiase & Dzansi, 2020;Fu et al, 2020;Marvel et al, 2020;You et al, 2021), human capital has a relationship with absorptive capacity (Ahmed et al, 2020;Bye & Faehn, 2022;Kato, 2020;Oliveira et al, 2020;Wu, 2020), and absorptive capacity has a relationship with product innovation (Akram et al, 2021;Coronado-Medina et al, 2020;Gallegos et al, 2020;Gao et al, 2022;Jeong et al, 2019). Therefore, it can be concluded that absorptive capacity has a moderating effect on the relationship between human capital and product innovation.…”
Section: Conceptual Frameworkmentioning
confidence: 83%
See 2 more Smart Citations